A Care Bundle Intervention to Prevent Surgical Site Infections After a Craniotomy. (28th June 2020) - Jiménez-Martínez, Emilio; Cuervo, Guillermo; Carratalà, Jordi; Hornero, Ana; Ciercoles, Pilar; Gabarrós, Andres; Cabellos, Carmen; Pelegrin, Ivan; Dominguez Luzón, Maria Angeles; García-Somoza, Dolores; Càmara, Jordi; Tebé, Cristian; et al.
Abstract: Background: Although surgical site infections after a craniotomy (SSI-CRANs) are a serious problem that involves significant morbidity and costs, information on their prevention is scarce. We aimed to determine whether the implementation of a care bundle was effective in preventing SSI-CRANs. Methods: A historical control study was used to evaluate the care bundle, which included a preoperative shower with 4% chlorhexidine soap, appropriate hair removal, adequate preoperative systemic antibiotic prophylaxis, the administration of 1 g of vancomycin powder into the subgaleal space before closing, and a postoperative dressing of the incisional surgical wound with a sterile absorbent cover. Patients were divided into 2 groups: preintervention (January 2013 to December 2015) and intervention (January 2016 to December 2017). The primary study end point was the incidence of SSI-CRANs within 1 year postsurgery. Propensity score matching was performed, and differences between the 2 study periods were assessed using Cox regression models. Results: A total of 595 and 422 patients were included in the preintervention and intervention periods, respectively. The incidence of SSI-CRANs was lower in the intervention period (15.3% vs 3.5%; P < .001). Using a propensity score model, 421 pairs of patients were matched. The care bundle intervention was independently associated with a reduced incidence of SSI-CRANs (adjusted odds ratio, 0.23; 95% confidence interval, .13–.40; P < .001). Conclusions: The care bundle intervention was effective in reducing SSI-CRAN rates. The implementation of this multimodal preventive strategy should be considered in centers with high SSI-CRAN incidences. Abstract : This historical control pre–post intervention study involving 1017 consecutive patients undergoing a craniotomy, who were carefully followed-up, found that the implementation of a preventive care bundle was highly effective in reducing the incidence of surgical site infections.